(untitled) (International Journal of Current Engineering and Technology, 2015)
In recent past, lead acid batteries have been by flywheels in the energy storage systems (ESS). The performance of a flywheel energy storage system (FESS) greatly depends on the performance of the supporting bearings. To study the performance of FESS incorporating ball bearings, a test setup was developed consisting of one 20 kg flywheel and two ball bearings. The performance of FESS was evaluated by measuring the time to coasting down of flywheel. With the number of operation of FESS, performance deterioration was observed. The condition monitoring unit, consisting of accelerometer and eddy current proximity sensor, was installed to investigate reason(s) of reduction in the performance. On analyzing acceleration and FFT plots, the failure of bearing(s) was diagnosed. To confirm the failure prediction, the bearing was dismantled and visual inspection was carried out.